Drug-induced liver injuries (part I) - S. F. Galimova (Трансплантология (Москва))
The paper describes current ideas on the mechanisms, classification, diagnosis, and treatment of drug-induced liver injuries (DILI). The latter masks all known acute and chronic liver diseases. Drugs are one of the leading causes of fulminant hepatic failure in many countries of the world. Early diagnosis and timely discontinuation of a drug that causes liver damage allow the disease progression to be prevented. The bases of DILD diagnosis are the careful collection of drug history data, the exclusion of other possible causes of liver damage, and the application of diagnostic scales (CIOMS/RUCAM).